The Death of Trust Across the U.S. Finance Industry - Peter Limbach; P. Raghavendra Rau; Henrik Schürmann (University of Cologne, Centre for Financial Research (CFR), 2020)
We document a significant decline in the level of generalized trust among finance professionals relative to the decline of trust in the general U.S. population. This decline occurs across all subsectors and at all hierarchy levels and is unique to the finance industry. It is related to a lack of confidence only in institutions that are relevant to the finance industry. The relative decline of trust is associated with a decreasing level of socialization among finance professionals as well as with changes in economic conditions and the professional environment in the finance industry.
Keywords: G20; G21; G22; G24; L14; A14; 330; Finance industry; Generalized trust; Implicit incentives; Professional environment; Socialization